2012
DOI: 10.1556/oh.2012.29364
|View full text |Cite
|
Sign up to set email alerts
|

Complications of systemic cytomegalovirus infection in therapy refracter Hodgkin’s lymphoma

Abstract: Cytomegalovirus infection related changes frequently remain masked by local symptoms of tumor invasion or therapeutic side effects in cancer patients. The spectrum of cytomegalovirus manifestations, however, can be highly varied and may contribute to the failure of different organs with fatal outcome. The case of a 29-year-old female patient is presented who obtained polychemotherapy and allogenic stem cell transplantation following the diagnosis of classical Hodgkin's disease. Despite intensified treatment, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Our results is near to what was found by (Irsai et al, 2012), his study showed similar results of BM infiltration & multiorgan affection in lymphoma patients associated with viral infection especially CMV, he observed cytopathic effect in multiple organs and significant hemophagocytosis was also observed in the spleen, liver and bone marrow. In summary, active cytomegalovirus infection may be a major cause of multi-organ failure in the immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 88%
“…Our results is near to what was found by (Irsai et al, 2012), his study showed similar results of BM infiltration & multiorgan affection in lymphoma patients associated with viral infection especially CMV, he observed cytopathic effect in multiple organs and significant hemophagocytosis was also observed in the spleen, liver and bone marrow. In summary, active cytomegalovirus infection may be a major cause of multi-organ failure in the immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 88%
“…Analyzing the cases reported in the literature, the median age of the patients was 40 years, and 50% occurred in postmenopausal women. All cases had associated immunosuppression: five cases (27.7%) were related to hematological malignancies 3 , 7 - 9 , 17 ; one (5.5%) was associated with glial neoplas 3 ; five (27.7%) was associated with carcinomas 3 , 10 , 12 , 15 , 16 ; one (5.5%) was associated with lupus glomerulonephritis 6 ; and six (33.6%; including the present report) were associated with AIDS. 2 , 4 , 11 , 13 , 14 In one case, CMV ovarian infection affected a fibrothecoma, which was present in one of the ovaries of a patient with refractory angioimmunoblastic non-Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have reported rapid clinical improvement of severe CMV infections in immunocompromised patients following antiviral therapy; however, the criteria for the use of specific antiviral drugs are not well established (6). There have been only 19 cases of CMV oophoritis reported, of which 3 were diagnosed by surgical resection, and the rest were diagnosed on autopsy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There have been no previous reports of treatment of CMV oophoritis with antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%